PENGARUH IKLAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN HP MERK VIVO DI TOKO DEVI CELL PASARWAJO KABUPATEN BUTON - Rahmatia, Devy; Pardana, Deki (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine the effect of social media advertising on purchasing decisions for Vivo brand cellphones at the Devi Cell store in Pasarwajo, Buton Regency. This research uses quantitative methods. Source of data in the form of primary data and secondary data. The population in this study were 416 people and the sample used was 77 respondents. Data analysis used validity test, reliability test, simple linear regression test, t-test (partial) and coefficient of determination.Based on the research results, it can be concluded that there is a positive and significant effect of social media advertising on purchasing decisions with the results of the partial test (t) where the t-count value (12.137) > t-table (1.665) and a significant value (0.000) < level value alpha (0.05). The magnitude of the influence of social media advertising on purchasing decisions is equal to 66,3% and the remaining 33.7% is influenced by other factors and variables not examined in this study